The role of intermediate cities in argentinan Pampa in the province of buenos aires regarding the structuration of Agrarian areas: An analysis of governance process in three municipalities - Albaladejo, Christophe Jacques (2017)
The Argentinan Pampa has an image of vast and expanded fields structured around large farms of cereals production or breeding units. However, in the Province of Buenos Aires, around the south of the capital, the urban network structures an area of the size of nearly half of France. These areas are managed around medium-sized cities, chief towns of the district (partido) seat of local government (intendancia) and municipal (municipio) with what they call « pueblos ». In a context of centralized government, the theme of decentralization is at the heart of the political debate: Municipalities ask for more responsibilities but they have very low budget. But a detailed analysis of different situations illustrates patterns of a contrasting management: First municipios who merely deal with the affairs directly related to the central government (Necochea et Villarino). On the other hand, we can observe a municipio which acts as a main character of local development (Tandil). In this perspective, they try to build a regional project by supporting two systems: One with a social dimension and another one around economic dimension to resolve serious social and economic problems.